A brief internet-delivered intervention for the reduction of gaming-related harm: A feasibility study - Jennifer J. Park (Elsevier, 2020)
Gaming Disorder is a recognised mental health condition with a very narrow range of treatment options. This pre-post study recruited 50 adult gamers from New Zealand to test the feasibility of a brief internet-delivered intervention. The intervention components were derived from Implementation Intention principles whereby the gap between intention and behaviour was targeted. The intervention delivery was in accordance with Self-Determination Theory to facilitate autonomy (personalised goals and action plans), competence (facilitated coping plans, self-monitoring, and relapse prevention) and relatedness (access to a goal coach providing written feedback and support to implement plans). Follow-up evaluation at 3-months indicated the intervention was feasible as it demonstrated rapid recruitment, program engagement (86% used the program), and high satisfaction (easy to understand and convenient). Plans most frequently focused on behavioural substitution and lifestyle change, and the most frequent barrier to change was time management followed by social pressure. Completers (n ​= ​35) reported a significant increase in well-being and reduction in severity, intensity, and time spent gaming, which reduced from an average of 29 to 11 ​hours per week. Delivery of a brief internet-delivered intervention shows promise and could be used to treat people experiencing problems who are unable or unwilling to access face-to-face treatment.